Impact of Ambient Air Pollution on Respiratory Symptoms, Lung Function, and Exacerbation Frequency Among Adult Residents of Lahore. A Cross-Sectional Clinical Study - ABBAS, MUHAMMAD UMAR ABBAS; ABBAS, AIMEN ABBAS; SAJJAD, MUHAMMAD SHAHZAIB; ALI, AKHTAR; AMJAD, SOHAIL; ABDULLAH, HARIS (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Lahore is a city that is continuously listed in the top ten in the world in terms of pollution, making the standards of the number of particles actually out of this scale. Air pollutants are a significant risk to respiratory health, and there are not many clinical data sets that relate exposure and functional impairment in the local population. Objective: The aim of the study is to determine the effects of air pollution on respiratory symptoms, lung function, and frequency of exacerbation in adult citizens of Lahore. Methods: A cross-sectional clinical study was performed on 300 adults who were recruited in high, moderate, and low pollution areas. Respiratory symptoms had been assessed through a structured question, exposure levels had been determined through AQI data and lung functioning assessed through spirometry in accordance with the guidelines of ATS/ESRS. The SPSS 26 was used to analyze the data with p < 0.05 being significant. Results: Respiratory symptoms were very high in high-exposure regions, such as cough (82.2%), throat irritation (75.3%), dyspnea (67.2%), and wheezing (48.9%). Spirometry revealed considerable changes in the FEV 1, FVC and FEV 1/FVC ratios between people in high-pollution regions (p < 0.001). High-exposure areas were also the areas with the highest respiratory exacerbation (56%). There was an apparent exposure response pattern on all outcomes. Conclusion: Respiratory health outcomes of ambient air pollution in Lahore are strongly negative, which leads to an increase in symptom burden, a decrease in lung functions, and the likelihood of exacerbations. There is a need to take urgent policy measures and community-level preventive interventions to curb the increasing health burden due to air pollution.